Transforming higher education and student engagement through collaborative review to inform educational design - von Konsky, Brian; Martin, Romana; Bolt, Susan; Broadley, Tania; Ostashewski, N. (ASCILITE, 2014)
This paper reports on staff perceptions arising from a review process designed to assist staff in making informed decisions regarding educational design, approaches to engage students in learning, and the technology to support engagement in the classroom and across multiple locations and delivery modes. The aim of the review process was to transform the level of student engagement in the business faculty of an Australian university. The process took a collaborative approach through consultation with academic staff involved in the design and delivery of the units under review, and included targeted professional development as necessary. An institutional framework that characterises engagement indicator contexts and their attributes facilitated dialog during the review process. This paper reports on a mixed method study that included a survey of participants, and purposeful interviews to evaluate the effectiveness of the process. Although the study identified factors that hindered implementation and operationalization of review recommendations in some instances, study participants were generally of the view that recommendations would enhance student engagement. It is demonstrated that the bottom-up approach described in this paper is consistent with theoretical frameworks for transformational change in teaching and learning and the adoption of innovations.